APPENDICULAR PERITONITIS IN CHILDREN - Abduvalieva Ch. M.; Usmanov Sh. M.; KhalilovSh. K. (Web of Journals Publishing, 2024)
Problems of diagnosis and treatment of appendiceal peritonitis in children are constantly in the focus of attention of pediatric surgeons. According to the literature, the course of acute appendicitis in children is complicated by the development of peritonitis in 8–10% of cases, while in children of the first three years of life, peritonitis is observed 4–5 times more often. The article discusses the same problem. The problem of treating peritonitis in children remains relevant due to the high incidence of this complication of acute appendicitis. The search for new methods of combating intra-abdominal infection and intestinal paresis does not stop. Total abscess peritonitis is the most severe form of appendiceal peritonitis, which is characterized by the formation of multiple encysted abscesses in the abdominal cavity, the development of sepsis syndromes and multiple organ failure, and often the transition to infectious-toxic shock by the time patients are admitted to the hospital. The main objectives of surgical intervention, in addition to appendectomy, for total abscess peritonitis are the sanitation of all encysted spaces, total resection of the omentum, intestinal decompression, dynamic control of the course of the inflammatory process in the abdominal cavity by creating a laparostomy according to indications.
Keywords: peritonitis, surgeon, method, treatment, diagnosis.